2005
DOI: 10.1007/s10974-005-9043-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled intermittent shortening contractions of a muscle–tendon complex: muscle fibre damage and effects on force transmission from a single head of rat EDL

Abstract: This study was performed to examine effects of prolonged (3 h) intermittent shortening (amplitude 2 mm) contractions (muscles were excited maximally) of head III of rat extensor digitorum longus muscle (EDL III) on indices of muscle damage and on force transmission within the intact anterior crural compartment. Three hours after the EDL III exercise, muscle fibre damage, as assessed by immunohistochemical staining of structural proteins (i.e. dystrophin, desmin, titin, laminin-2), was found in EDL, tibialis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…MLP interacts with titin through T-cap. In rodents, increased mRNA expression of MLP has been observed 6 h after lengthening muscle actions (5) and 3 h after prolonged concentric contractions (34). In the present study, the increase in the mRNA levels of MLP was observed 2 days postexercise.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…MLP interacts with titin through T-cap. In rodents, increased mRNA expression of MLP has been observed 6 h after lengthening muscle actions (5) and 3 h after prolonged concentric contractions (34). In the present study, the increase in the mRNA levels of MLP was observed 2 days postexercise.…”
Section: Discussionsupporting
confidence: 65%
“…This is the first study to show increased CARP mRNA expression after physical exercise in human skeletal muscle. In rodents, increased mRNA expression CARP has been observed 6 h after lengthening muscle actions (5) and 3 h after prolonged concentric contractions (34). We observed increased CARP mRNA expression as early as 30 min postexercise, which can be regarded as an extremely rapid response.…”
Section: Discussionsupporting
confidence: 48%
“…However this resulted in significantly lower torque only during the latter. High shear forces of the muscle connective tissue has been suggested to occur especially during eccentric (Kjaer, 2004) but also concentric contraction (Maas et al, 2005). Together, this may explain that differences were more consistent during slow concentric and eccentric contraction.…”
Section: Discussionmentioning
confidence: 88%
“…Isokinetic dynamometry at various contraction modes and velocities as opposed to static contraction alone can be used to more completely evaluate strength capacity. Both concentric and eccentric contractions have been suggested to involve high shear forces of the muscle connective tissue (Maas et al, 2005;Kjaer, 2004). Furthermore, concentric compared with static contraction involves higher cross-bridge cycling rate, energy expenditure and fatigue (Woledge et al, 1985;Vedsted et al, 2003), and eccentric contraction has been associated with ultra-structural muscle damage (Proske and Allen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have hypothesized the key role of deep fascia in coordinating muscular activity [42], and in the literature, there is growing evidence [43][44][45][46] that this tissue plays a role in "limb stability, force transmission, and elastic energy storage during locomotion." In the past years, many efforts have been made to develop biomechanical models to assist in deciphering the fascia function and help in understanding how alterations of the deep fascia can result in musculoskeletal disorders and pain [3,18,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%